Update on the Economic Impact of the 2014-2015 Ebola Epidemic on Liberia, Sierra Leone, and Guinea - World Bank Group (World Bank, Washington, DC, 2015)
A year after the onset of Ebola, the estimated GDP losses for the three countries through 2015 total US$2.2 billion (US$240 million for Liberia, US$535 million for Guinea and US$1.4 billion for Sierra Leone). This is the result of the severe impact of the epidemic which has been exacerbated by the large decline in the world price of iron ore and severe corporate governance issues in mining in Sierra Leone. Important differences among the three countries are emerging. Liberia is gradually returning to normalcy, Guineas economy is stagnating, and Sierra Leone is suffering a severe recession. This update presents the World Banks most recent analysis of the economic and fiscal effects of the Ebola epidemic on the three countries. In relation to our January 2015 report it contains: 1) an updated status for the economies of Liberia, Guinea, and Sierra Leone; and 2) a brief description of these countries Economic Recovery Plans with indicative estimates of their potential impact on growth. As of April 2015, the Ebola epidemic has been largely contained but the negative effects on the economies of Liberia, Guinea and Sierra Leone loom large amidst continued uncertainty about the timing of complete eradication. The crisis continues to adversely affect these economies, so pace of recovery in these countries will depend heavily on adequate financing and effective implementation of the recovery plans. Ultimately, Liberia, Guinea and Sierra Leone will need the strong support from the development community over the next years to both make up for the losses incurred during the Ebola crisis and make these economies less vulnerable for the future.